Answer

Verified

402.3k+ views

**Hint:**We have to find the value of \[x\]. For this, first, we need to simplify the given equation.

To solve the equation, we will apply a few formulae as follows:

\[{a^{m + n}} = {a^m}.{a^n}\]

\[{a^{{{\log }_a}x}} = x\]

We know that, if the multiplication of two terms is zero, the value of each term is individually zero.

**Complete step by step answer:**

It is given that, \[{9^{1 + \log x}} - {3^{1 + \log x}} - 210 = 0\] the base is \[3\].

We have to find the value of \[x\].

Here, we have,

\[ \Rightarrow {9^{1 + \log x}} - {3^{1 + \log x}} - 210 = 0\]

We know that,

\[ \Rightarrow {a^{m + n}} = {a^m}.{a^n}\]

Applying the formula, we get,

\[ \Rightarrow {9.9^{\log x}} - {3.3^{\log x}} - 210 = 0\]

Simplifying we get,

\[ \Rightarrow {9.3^{2\log x}} - {3.3^{\log x}} - 210 = 0\]

Since, the base is \[3\]. We have, \[{3^{\log x}} = x\]

So, applying the formula we get,

\[ \Rightarrow 9{x^2} - 3x - 210 = 0\]

Dividing each term by \[3\] we get,

\[ \Rightarrow 3{x^2} - x - 70 = 0\]

Now we will split the middle term as follows,

\[ \Rightarrow 3{x^2} - 15x + 14x - 70 = 0\]

Simplifying we get,

\[ \Rightarrow 3x(x - 5) + 14(x - 5) = 0\]

Simplifying again we get,

\[ \Rightarrow (x - 5)(3x + 14) = 0\]

We know that, if the multiplication of two terms is zero, the value of each term is individually zero.

So, we have,

\[ \Rightarrow (x - 5) = 0\] gives \[x = 5\] and

\[ \Rightarrow (3x + 14) = 0\] gives \[x = \dfrac{{ - 14}}{3}\]

We only take positive value for $x$ as the logarithm of negative numbers is not defined.

**$\therefore $ The value of \[x\] is \[5\].**

**Note:**

In Quadratic Factorization using Splitting of Middle Term which is \[x\] term is the sum of two factors and product equal to the last term.

Logarithm, the exponent or power to which a base must be raised to yield a given number. Expressed mathematically, \[x\] is the logarithm of \[n\] to the base \[b\] if \[{b^x} = n\], in which case one writes \[x = {\log _b}n\].

When rewriting an exponential equation in log form or a log equation in exponential form, it is helpful to remember that the base of the logarithm is the same as the base of the exponent.

Recently Updated Pages

The base of a right prism is a pentagon whose sides class 10 maths CBSE

A die is thrown Find the probability that the number class 10 maths CBSE

A mans age is six times the age of his son In six years class 10 maths CBSE

A started a business with Rs 21000 and is joined afterwards class 10 maths CBSE

Aasifbhai bought a refrigerator at Rs 10000 After some class 10 maths CBSE

Give a brief history of the mathematician Pythagoras class 10 maths CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Name 10 Living and Non living things class 9 biology CBSE

Select the word that is correctly spelled a Twelveth class 10 english CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Write the 6 fundamental rights of India and explain in detail